The application of high resolution diffusion NMR for the characterisation and quantification of small molecules in saliva/dentifrice slurries. Issue 6 (21st March 2015) - Le Gresley, Adam; Simpson, Emma; Sinclair, Alex J.; Williams, Neil; Burnett, Gary R.; Bradshaw, Dave J.; Lucas, Robert A.
<x xml:space="preserve">Abstract</x> The application of DOSY NMR as a technique for the virtual separation of toothpaste adjuvants in model saliva is reported for the first time.